TMT Exacerbates Selenium-Deficient Enteritis in Gallus by Mediating Pyroptosis Through ROS/ERS - Shize Wang; Yutian Lei; Yuting Dong; Kang Yang; Tong Xu; Hongjin Lin (Biological Trace Element Research, 2026)

Selenium regulates pyroptosis through the ROS-mtDNA-cGAS-STING axis to alleviate trimethyltin chloride-induced inflammation in chicken kidneys - Huiling Zheng; Xinyu Huo; Wenwen Zhang; Shuang Lou; Mingyue Li; Chenxi Huang; Kang Yang; Tong Xu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Electrostatic spinning technology coupled with traditional pollution control processes: A review - Hanrun Lv; Xuechen Li; Mengjiao Wang; Ruyu Bai; Hongjin Li; Junlang Lao; Mengda Du; Jiaqi Shi; Hanfei Gao; Baorong Duan; Qingjian Zhang; Lin Liu; et al. (Science of The Total Environment, 2025)

Exploring the modification of dietary fiber from black highland barley bran based on machine learning and metabolomics - Minhao Xu; Hongjin Ning; Zhijun Wu; Hong Chen; Wen Qin; Derong Lin (Journal of Cereal Science, 2025)

SiO2 NP promotes allergic gastritis induced by degranulation of mouse MC9 cell through AQP4-mediated impairment of SIRT3-TFAM deacetylation and mitochondrial autophagy - Yutian Lei; Xiaodan Wang; Hao Wu; Meichen Gao; Tong Xu; Hongjin Lin (Journal of Hazardous Materials, 2025)

Soil Carbon‐to‐Nitrogen Ratio Can Predict the Grassland Biodiversity‐Productivity Relationship: Evidence From Local, Regional, and Global Scales - Hongjin Zhang; Lin Jiang; Wei Wang (Global Change Biology, 2025)
Soil elemental stoichiometry serves as an inherent link between soil biogeochemistry and the structure and processes within plant communities, and thus is at the core of ecosystem functions. Yet, the regulatory role of soil stoichiometry, particularly the carbon‐to‐nitrogen (C:N) ratio, in shaping biodiversity‐productivity relationships remains poorly understood. By integrating data from our regional field surveys (58 sites) and a local complementary N addition experiment in temperate grasslands, together with a global grassland dataset (74 sites), here we showed that plant productivity exhibited a unimodal response to increasing soil C:N ratios, with peaking values at the C:N ratio of approximately 15. At this critical value, the determinants driving grassland productivity undergo a fundamental shift: below the soil C:N of 15, plant diversity was positively related to productivity, while above this threshold, bacterial and fungal diversity showed a positive linkage with plant productivity. This divergence implies a stoichiometric “switch” in biodiversity‐productivity relationships: high soil C:N ratios strengthen the reliance of productivity on soil bacterial and fungal diversity to mitigate N deficiency, while low C:N ratios shift the emphasis to plant diversity to exploit resource‐rich environments. Our findings highlight that soil stoichiometry can predict biodiversity‐productivity relationships, with important implications for grassland restoration and management.

Corrigendum to “BPA and low-Se exacerbate apoptosis and autophagy in the chicken bursa of Fabricius by regulating the ROS/AKT/FOXO1 pathway” [Science of the Total Environment 2024 (908) 168424] - Wenying Sun; Tong Xu; Hongjin Lin; Yilin Yin; Shiwen Xu (Science of The Total Environment, 2025)

Comparative Analysis of Different Body Composition, Mucus Biochemical Indices, and Body Color in Five Strains of Larimichthys crocea - Hongjin Deng; Quanyou Guo; Banghong Wei; Jiehui Zhong; Mengyao Zheng; Yao Zheng; Na Lin; Shengyang Zheng (Fishes, 2025)
The large yellow croaker, or Larimichthys crocea, is highly prized for its golden color and nutritional content. The purpose of this study was to investigate the differences in body composition, mucus biochemical indices and body color in five strains of large yellow croakers (body weight: 347.01 ± 5.86 g). To conduct genetic diversity analyses of the populations, a total of 50 tailfin samples were randomly chosen from the following populations of large yellow croakers: wild (LYC1), Dai-qu population (LYC2), Yongdai 1 (LYC3), Min-yuedong population (LYC4), and Fufa 1 (LYC5). The findings demonstrated that the LYC3 group’s pigment contents, crude protein, crude lipid, and chromatic values were comparable to those of the LYC1 group (p > 0.05). There was no significant difference between the LYC1 and LYC5 groups’ mucus superoxide dismutase (SOD) and catalase (CAT) activities (p > 0.05). The alkaline phosphatases (ALP), acid phosphatases (ACP), and lysozyme (LYS) activities of the mucus in the LYC1 group were not significantly different from the LYC3 group (p > 0.05). The back skin mRNA expressions of tyrosinase (tyr), tyrosinase-related protein 1 (tyrp1), dopachrome tautomerase (dct), microphtalmia-associated transcription factor (mitf), and melanocortin 1 receptor (mc1r) were significantly up-regulated in the LYC2 and LYC4 groups compared to the LYC1, LYC3, and LYC5 groups (p

Natural promising daphnane diterpenoids: An integrated review of their sources, structural classification, biological activities, and synthesis - Kang Ding; Xuege Pan; Weifeng Yin; Lin Li; Hongjin Bai; Maoli Bai; Jiekun Xu; Jun He; Weiku Zhang (Phytochemistry, 2025)

New insights into quercetin's attenuation of TBBPA-induced injury to MCEC cells: Involvement of the p38/NF-κB pathway and pyroptosis - Ke Li; Kun Wang; Tong Xu; Chencong Lyu; Xuejiao Yang; Hongjin Lin; Shiwen Xu (Journal of Environmental Management, 2025)

Selenium deficiency exacerbates ROS/ER stress mediated pyroptosis and ferroptosis induced by bisphenol A in chickens thymus - Kun Wang; Xu Shi; Hongjin Lin; Tong Xu; Shiwen Xu (Journal of Environmental Sciences, 2025)

MEHP induced mitochondrial damage by promoting ROS production in CIK cells, leading to apoptosis, autophagy, cell cycle arrest - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Mechanism of promoting okara insoluble to soluble dietary fiber by high-pressure homogenization-microbial fermentation - Derong Lin; Hongjin Ning; Ya Liu; Wen Qin; Jianhua Liu; Douglas A. Loy (Bioresource Technology, 2025)

Resveratrol alleviates Mono-2-ethylhexyl phthalate-induced mitophagy, ferroptosis, and immunological dysfunction in grass carp hepatocytes by regulating the Nrf2 pathway - Xiaodan Wang; Meichen Gao; Xiunan Lu; Yutian Lei; Jiatong Sun; Mengyao Ren; Tong Xu; Hongjin Lin (Journal of Environmental Management, 2024)

Quercetin antagonizes apoptosis, autophagy and immune dysfunction induced by di(2-ethylhexyl) phthalate via ROS/ASK1/JNK pathway - Jiatong Sun; Xiaodan Wang; Tong Xu; Mengyao Ren; Meichen Gao; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Emamectin benzoate exposure induced carp kidney injury by triggering mitochondrial oxidative stress to accelerate ferroptosis and autophagy - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Pesticide Biochemistry and Physiology, 2024)

Targeted and untargeted metabolomics reveals meat quality in grazing yak during different phenology periods on the Qinghai-Tibetan Plateau - Tongqing Guo; Qian Zhang; Xungang Wang; Xianli Xu; Yalin Wang; Lin Wei; Na Li; Hongjin Liu; Linyong Hu; Na Zhao; Shixiao Xu (Food Chemistry, 2024)

Bisphenol A Regulates the TNFR1 Pathway and Excessive ROS Mediated by miR-26a-5p/ADAM17 Axis to Aggravate Selenium Deficiency-Induced Necroptosis in Broiler Veins - Xue Fan; Yixuan Wang; Jintao Zhang; Hongjin Lin; Zhikun Bai; Shu Li (Biological Trace Element Research, 2024)

Effects of atrazine and curcumin exposure on TCMK-1 cells: Oxidative damage, pyroptosis and cell cycle arrest - Mengyao Ren; Xiunan Lv; Tong Xu; Jiatong Sun; Meichen Gao; Hongjin Lin (Food and Chemical Toxicology, 2024)

Selenium deficiency exacerbated Bisphenol A-induced intestinal toxicity in chickens: Apoptosis and cell cycle arrest mediated by ROS/P53 - Dongliu Luo; Xinyu Tang; Yixuan Wang; Shuqi Ying; Yujiao He; Hongjin Lin; Pervez Ahmed Khoso; Shu Li (Science of The Total Environment, 2024)

Spatiotemporal differentiation and attribution of land surface temperature in China in 2001–2020 - Hao Tian; Lin Liu; Zhengyong Zhang; Hongjin Chen; Xueying Zhang; Tongxia Wang; Ziwei Kang (Journal of Geographical Sciences, 2024)

BPA and low-Se exacerbate apoptosis and autophagy in the chicken bursa of Fabricius by regulating the ROS/AKT/FOXO1 pathway - Wenying Sun; Tong Xu; Hongjin Lin; Yilin Yin; Shiwen Xu (Science of The Total Environment, 2024)

New insights into brain injury in chickens induced by bisphenol A and selenium deficiency—Mitochondrial reactive oxygen species and mitophagy-apoptosis crosstalk homeostasis - Huanyi Liu; Hongjin Lin; Tong Xu; Xu Shi; Yujie Yao; Pervez Ahmed Khoso; Zhihui Jiang; Shiwen Xu (Science of The Total Environment, 2023)

TBBPA and lead co-exposure induces grass carp liver cells apoptosis via ROS/JAK2/STAT3 signaling axis - Lu Li; Wan Li; Yufeng Liu; Xin Jin; Yanbo Yu; Hongjin Lin (Fish & Shellfish Immunology, 2023)

Selenium alleviates lead-induced CIK cells pyroptosis and inflammation through IRAK1/TAK1/IKK pathway - Xiunan Lv; Mengyao Ren; Tong Xu; Meichen Gao; Huanyi Liu; Hongjin Lin (Fish & Shellfish Immunology, 2023)

Spatio-temporal pattern and attribution analysis of the mass elevation effect in the Tianshan Mountains in China - Mingyu Zhang; Zhengyong Zhang; Lin Liu; Xueying Zhang; Ziwei Kang; Hongjin Chen; Yu Gao; Tongxia Wang; Fengchen Yu (Journal of Geographical Sciences, 2023)

Evodiamine alleviates DEHP-induced hepatocyte pyroptosis, necroptosis and immunosuppression in grass carp through ROS-regulated TLR4 / MyD88 / NF-κB pathway - Yutian Lei; Tong Xu; Wenying Sun; Xiaodan Wang; Meichen Gao; Hongjin Lin (Fish & Shellfish Immunology, 2023)

Roles of selenoprotein K in oxidative stress and endoplasmic reticulum stress under selenium deficiency in chicken liver - Wenyue Zhang; Xinyue Sun; Yutian Lei; Xiaojing Liu; Yilei Zhang; Yuqi Wang; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Mechanism of evodiamine blocking Nrf2/MAPK pathway to inhibit apoptosis of grass carp hepatocytes induced by DEHP - Yutian Lei; Wenyue Zhang; Meichen Gao; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Bisphenol A exacerbates selenium deficiency-induced pyroptosis via the NF-κB/NLRP3/Caspase-1 pathway in chicken trachea - Kexin Yin; Xinyue Sun; Yaxin Zheng; Wenyue Zhang; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Subacute Cadmium Exposure Induces Necroptosis in Swine Lung via Influencing Th1/Th2 Balance - Wenyue Zhang; Xinyue Sun; Xu Shi; Xue Qi; Shaoqian Shang; Hongjin Lin (Biological Trace Element Research, 2023)

Cadmium induces apoptosis by miR-9-5p targeting PTEN and regulates the PI3K/AKT pathway in the piglet adrenal gland - Xue Qi; Zeheng Ren; Yuan Cui; Jinxi Zhang; Yue Zhang; Shengchen Wang; Hongjin Lin (Environmental Science and Pollution Research, 2022)

Spatio-temporal correlation between human activity intensity and land surface temperature on the north slope of Tianshan Mountains - Hongjin Chen; Lin Liu; Zhengyong Zhang; Ya Liu; Hao Tian; Ziwei Kang; Tongxia Wang; Xueying Zhang (Journal of Geographical Sciences, 2022)

TRAF2/ASK1/JNK Signaling Pathway Is Involved in the Lung Apoptosis of Swine Induced by Cadmium Exposure - Jinxi Zhang; Yue Zhang; Xue Qi; Yuan Cui; Xiaoming Chen; Hongjin Lin (Biological Trace Element Research, 2022)

The Protective Effect of Selenium on the Chicken Pancreas against Cadmium Toxicity via Alleviating Oxidative Stress and Autophagy - Ruohan Liu; Tiantian Jia; Yuan Cui; Hongjin Lin; Shu Li (Biological Trace Element Research, 2018)

Selenium Supplementation Changes the Ion Profile in the Pancreas of Chickens Treated with Cadmium - Rongkun Bao; Xinyue Wang; Shufang Zheng; Qiaojian Zhang; Hongjin Lin; Shu Li (Biological Trace Element Research, 2018)

Role of Hydrogen Sulfide on Autophagy in Liver Injuries Induced by Selenium Deficiency in Chickens - Wang Wenzhong; Zhang Tong; Lin Hongjin; Chang Ying; Xing Jun (Biological Trace Element Research, 2017)

Ameliorative Effects of Selenium on Cadmium-Induced Oxidative Stress and Endoplasmic Reticulum Stress in the Chicken Kidney - Lili Liu; Bingyou Yang; Yupeng Cheng; Hongjin Lin (Biological Trace Element Research, 2015)